2022
DOI: 10.7150/jca.66978
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent Immunotoxins Targeting the Membrane-distal N-lobe of GPC3 for Immunotherapy of Hepatocellular Carcinoma

Abstract: Glypican-3 (GPC3) has become a compelling target for immunotherapy of hepatocellular carcinoma, including antibody-drug conjugate (ADC), and ADC-like immunotoxin. To investigate the impact of epitopes on the potency of ADCs, current study generated a large panel of chicken monoclonal antibodies (mAbs) that targeted 12 different and over-lapping epitopes on GPC3. These mAbs demonstrated a very high affinity with Kd values in the range of 10 -9 -10 -14 M, and the highest affinity (Kd value of 0.0214 pM) was 40-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Previous studies have revealed that PE24 caused the modification of eukaryotic elongation factor-2 and induced cell death by apoptosis or pyroptosis. 13,40,41 In our studies, we noted that the dying cells triggered by T22-PE24 showed evident cell swelling and giant bubbles from the plasma membrane (Fig. 3E), which are the typical characteristics of pyroptosis.…”
Section: Resultsmentioning
confidence: 61%
“…Previous studies have revealed that PE24 caused the modification of eukaryotic elongation factor-2 and induced cell death by apoptosis or pyroptosis. 13,40,41 In our studies, we noted that the dying cells triggered by T22-PE24 showed evident cell swelling and giant bubbles from the plasma membrane (Fig. 3E), which are the typical characteristics of pyroptosis.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, these tumor cell membrane proteins were either highly expressed in tumors or prognostic risk factors for tumor patients. Furthermore, some of them have been proven to be drug targets in solid tumors, such as GPC3 in liver cancer [ 36 ], MSLN in gastric cancer, and EGFR in glioma ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…When tumor formed and reached a volume of 100-200 mm 3 , mice were randomly divided into different treatment groups according to the mean tumor volume, with ve mice each group. Treatment of mice was accomplished by intratumoral injections of EGFRvIII Immunotoxin R6-PE24, and GPC3-targeted immunotoxin HN3-PE24, which was previously generated in our lab [30], was served as a control. Tumor dimensions were measured by Vernier calipers every 2 to 3 days.…”
Section: Subcutaneous Xenograft Mouse Modelmentioning
confidence: 99%